Muslim Women, Islamic Education, and TikTok: Achieving Gender Equality and Combating Cyberbullying - Asti Triasih; Zuhdiyah Zuhdiyah; Maryamah Maryamah (FKIP - Universitas Riau, 2026)
In the digital era, TikTok has become a significant medium for Indonesian Muslim women to express their identities and advocate for gender equality through content that challenges stereotypes and builds supportive communities. This study aims to analyze how Muslim women utilize TikTok as a form of da’wah and self-empowerment while facing the challenges of cyberbullying and moral criticism. Using a qualitative research method with a literature review approach, data were collected from relevant academic studies, social media analyses, and documentation of user experiences. The findings reveal that Muslim women dynamically represent their religious identity by integrating Islamic values with progressive and modern expressions, showing that faith and modernity can coexist harmoniously. Through educational, inspirational, and community-based content, they promote gender equality, financial literacy, and inclusive dialogue about women’s roles in religion and society. Despite these positive contributions, they still encounter serious challenges such as online harassment, gender-based discrimination, and digital violence. The study concludes that resilience, community solidarity, and the implementation of digital literacy and protection strategies are crucial for ensuring a safe and empowering online space for Muslim women and other marginalized groups.